FEATURES OF HUNGER 1921-1922 IN KAZAKHSTAN AND ITS CONSEQUENCES - Малабаев, С.К.; Козыбаева, М.М. (Asian Journal "Steppe Panorama", 2025)
The article is devoted to the famine of 1921-1922 in Kazakhstan. In the article, the authors reveal the causes and consequences of the famine of 1921-1922 in Kazakhstan, which, in comparison with other affected regions, experienced a greater burden in terms of food security. The famine was aggravated by the devastation and anarchy during the civil war, which prevented the rapid resolution of problems. In the north-western regions of Kazakhstan, famine became possible not only as a result of a natural disaster, but also as a result of the removal of surplus agricultural products by food detachments. The Kazakh people suffered from hunger, especially due to fundamental changes in the economy and a reduction in the number of livestock. The authors come to the conclusion that, although assistance to the hungry was provided, it was clearly insufficient, they show the role of international organizations in the fight against hunger.